Comparison of Computerized Tomographic Angiography (CTA) and Digital Subtraction Angiography (DSA) in patients with subarachnoid hemorrhage: A retrospective analysisy (Annals of Medical Research, 2021)
Aim: Aneurysmal subarachnoid hemorrhage (SAH) is one of the most complex conditions encountered in neurosurgery clinics. It is aimed to compare Computerized Tomographic Angiography (CTA) and Digital Subtraction Angiography (DSA) techniques for detecting aneurysms of anterior communicating artery (AcomA) and middle cerebral artery (MCA) in the present study.Materials and Methods: The medical files of 20 patients with aneurysmal SAH who had both CTA and DSA scans were included in the study. Raw data of tomographic images was re-created as 3D reconstructions by using computer.Results: Mean age of the patients was 55.5 years (min-max: 27-82 years). Nine of the patients were male (45%) and 11 were female (55%). Mostly, the results obtained by CTA imaging were confirmed by DSA. No significant differences were detected between CTA and DSA methods regarding to dome area and size of aneurysms of both AcomA and MCA (p>0.05). Conclusion: Both methods can be implemented in clinical settings for detecting SAK.